IgM flow assay for detection of Typhoid Fever (Bangladesh Journal of Medical Microbiology, 2012)
A case-control study was carried out in the Department of Microbiology & Immunology at BSMMU, Dhaka from July 2007 to June 2008 to validate IgM flow assay commercial diagnostic kits to assess the usefulness for the rapid diagnosis of typhoid fever. A total of 437 febrile patients clinically suspected of having typhoid fever were studied. Sixty cases were taken as controls, in which 30 were febrile controls (non-typhoidal febrile illness) and 30 were healthy controls. Among these 437 patients, Salmonella typhi was isolated from 58 (13.27%) cases .The isolation rate of S.typhi from blood was higher 21 (22.34%) in pediatric age group than that of the adult 37(10.78%); which is statistically significant (P